2006
DOI: 10.1534/genetics.105.049577
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic UNC-31 (CAPS) Is Required to Activate the Gαs Pathway of the Caenorhabditis elegans Synaptic Signaling Network

Abstract: C. elegans mutants lacking the dense-core vesicle priming protein UNC-31 (CAPS) share highly similar phenotypes with mutants lacking a neuronal Ga s pathway, including strong paralysis despite exhibiting near normal levels of steady-state acetylcholine release as indicated by drug sensitivity assays. Our genetic analysis shows that UNC-31 and neuronal Ga s are different parts of the same pathway and that the UNC-31/Ga s pathway is functionally distinct from the presynaptic Ga q pathway with which it interacts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
119
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(128 citation statements)
references
References 50 publications
7
119
2
Order By: Relevance
“…We prepared freeze-cracked 4% paraformaldehyde fixed worms for immunostaining as described (Charlie et al 2006a;Charlie et al 2006b), with the exception that we fixed worms for anti-FMRFamide staining for 16 h at 6° C . For immunostaining of FMRFamide neuropeptides, we co-immunostained N2 and unc-43(ce685) fixed animals using Rabbit antiFMRFamide antiserum (1/2000) and Goat anti-UNC-47 antiserum (1/12,000) ), using Donkey anti-Rabbit Dylight 550 and Donkey anti-Goat Dylight 488 secondary antibodies (Pierce).…”
Section: Immunostainingmentioning
confidence: 99%
See 1 more Smart Citation
“…We prepared freeze-cracked 4% paraformaldehyde fixed worms for immunostaining as described (Charlie et al 2006a;Charlie et al 2006b), with the exception that we fixed worms for anti-FMRFamide staining for 16 h at 6° C . For immunostaining of FMRFamide neuropeptides, we co-immunostained N2 and unc-43(ce685) fixed animals using Rabbit antiFMRFamide antiserum (1/2000) and Goat anti-UNC-47 antiserum (1/12,000) ), using Donkey anti-Rabbit Dylight 550 and Donkey anti-Goat Dylight 488 secondary antibodies (Pierce).…”
Section: Immunostainingmentioning
confidence: 99%
“…We dual-labeled the GFP with Donkey anti-Mouse Dylight 488 and Donkey anti-Mouse Dylight 650 secondaries, and we labeled the EGL-21 primary antibody with a Donkey anti-Rabbit Dylight 550 secondary. For immunostaining of UNC-31 (CAPS), we triple-stained wild type and unc-43(ce685) fixed animals using Goat anti-UNC-31 (1/200; KM16C-3.1; Charlie et al, 2006a), Mouse anti-UNC-17 (1/5000 from monoclonal ascites fluid; , and Rabbit anti-UNC-10 (1/240; RIM5431; (Koushika et al 2001). We used previously described methods for immunostaining of fixed animals (Charlie et al 2006a;Charlie et al 2006b), with the exception that we only spread 750 animals per slide at the final mounting step.…”
Section: Immunostainingmentioning
confidence: 99%
“…The unc-17 promoter (Punc-17) included 3180 bp upstream of the SL1 trans-splice site (Alfonso et al 1994a); it drives expression exclusively in cholinergic neurons (Rand et al 2000). A derivative of this promoter, designated Punc-17b, drives expression in the AS, DA, DB, VA, and VB cholinergic motor neurons of the ventral nerve cord (Charlie et al 2006).…”
Section: Transgene Production and Propertiesmentioning
confidence: 99%
“…The unc-17 promoter (Punc-17) included 3180 bp upstream of the SL1 trans-splice site (Alfonso et al 1994a); it drives expression exclusively in cholinergic neurons (Rand et al 2000). A derivative of this promoter, designated Punc-17b, drives expression in the AS, DA, DB, VA, and VB cholinergic motor neurons of the ventral nerve cord (Charlie et al 2006).DNA injections: Transgenic nematodes were generated by microinjection of DNA (plasmids and/or PCR products), essentially as described by Mello and Fire (1995). The final DNA concentration was adjusted to 50 ng/ml by the addition of pBluescript.…”
mentioning
confidence: 99%
“…Ga q (C. elegans EGL-30) and Ga s (GSA-1) positively influence neurotransmitter release while Ga o (GOA-1) activity reduces neurotransmitter release through inhibition of the Ga q /EGL-30 pathway (HajduCronin et al 1999;Lackner et al 1999;Miller et al 1999;Reynolds et al 2005;Schade et al 2005;Charlie et al 2006). Our previous genetic analysis placed unc-73 RhoGEF-2 activity downstream of Ga o /GOA-1 and Williams et al (2007) more specifically identified the UNC-73E RhoGEF-2 isoform as a Ga q /EGL-30 effector acting in parallel to phospholipase C b (EGL-8) (Steven et al 2005).…”
mentioning
confidence: 99%